Reverse Engineering : Technology of Reinvention - Wang, Wego (USA : CRC Press, 2011)
The process of reverse engineering has proven infinitely useful for analyzing Original Equipment Manufacturer (OEM) components to duplicate or repair them, or simply improve on their design. A guidebook to the rapid-fire changes in this area, Reverse Engineering: Technology of Reinvention introduces the fundamental principles, advanced methodologies, and other essential aspects of reverse engineering.
Keywords: Reverse Engineering; Technology of Reinvention